Beyond climate economics orthodoxy: Impacts and policies in the agent-based integrated-assessment DSK model - Francesco Lamperti; Andrea Roventini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2022)
Though climate physical and transition risks will likely affect socio-economic dynamics along any transition pathways, their unfolding is still poorly understood. This also affects the development of climate-change policies to achieve sustainable growth. In this paper, we discuss a series of results assessing the materiality of climate risks for economic and financial stability and alternative policy pathways by means of the Dystopian Schumpeter meeting Keynes (DSK) agent-based integrated assessment model. Our results suggest the emergence of tipping points wherein physical risks under unmitigated emissions will reduce long-run growth and spur financial and economic instability. Moreover, diverse types of climate shocks have a different impact on economic dynamics and on the chances of observing a transition to carbonless growth. While these results call for immediate and ambitious interventions, appropriate mitigation policies need to be designed. Our results show that carbon taxation is not the most suitable tool to achieve zero-emission growth given its huge economic costs. On the contrary, command-and-control regulation and innovation policies to foster green investments is the best policy mix to put the economy on a green growth pathway. Overall, our results contradict the standard tenets of cost-benefit climate economics and suggest the absence of any trade-off between decarbonization and growth.
Keywords: C63; Q40; Q50; Q54; 330; climate policy; climate risks; macroeconomic dynamics; agent-based modelling